Examining the performance of ant colony optimization on shortest path problem: (Aegean sea example) [En Kisa Yol Problemi Üzerinde Karinca Kolonisi Algoritmasinin Performansinin Incelenmesi (Ege Denizi Örneǧi)] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2018)
The ant colony algorithm is an intuitive algorithm and one of the most frequently used problem solving algorithms. The problem of finding the shortest route is an important subject in important areas such as shipping, aviation, defense and freight forwarding. The study carries out the use of the ant colony algorithm on a route decision support system. In this study the shortest path was determined by the ant colony algorithm in the decision making stage to go from one node to the other on the Aegean sea. The results obtained are examined in terms of time, accuracy, and factors affecting the performance of the ant colony algorithm like pheromone amount, pheromone update, influence coefficents of pheromone and tour distance of ants. © 2018 IEEE.
Keywords: Aegean Sea; Ant colony algorithm; optimization; shortest path